SCHOOL LIBRARY IN THE SERVICE OF INFORMATION AND MEDIA LITERACY OF STUDENTS (Heritage, 2023)
The article deals with the role that the school library plays in the information and media literacy of students, with a special emphasis on digital libraries used for this purpose. In the first part of the article, a brief overview of the changes in the school library collection brought about by new information and communication technologies was given. In addition to printed library materials, the school library increasingly owns digital media, which makes it the multimedia center of the school. The importance of digital media in teaching is emphasized through the presentation of the possibility of their application. Also, the views of various authors on the application of digital media in education are presented. The second part of the article examines the importance of the digital library in the information and media literacy of students. The most important role in this is played by school librarians who train students to find information on their own, to valorize and use it effectively. In addition, they help students create, analyze and evaluate media content.
Keywords: school library, digital media, digital libraries, information literacy, media literacy.